Clear‐Box Machine Learning for Virtual Screening of 2D Nanozymes to Target Tumor Hydrogen Peroxide (Adv. Healthcare Mater. 10/2023). Issue 10 (17th April 2023) - Gao, Xuejiao J.; Yan, Jun; Zheng, Jia‐Jia; Zhong, Shengliang; Gao, Xingfa
Abstract : Tumor Therapy In article 2202925 by Xingfa Gao and co‐workers, an efficient computer‐aided method is developed to virtually select materials from a 2D materials library for cancer chemotherapy. Targeting tumor H2 O2, the selected enzyme‐like nanomaterials present intrinsic peroxidase‐ or catalase‐mimicking activities and thus can improve the efficiency of chemodynamic therapy (CDT) and relieve tumor hypoxia. The strategy is expected to promote the development of catalytic nanomaterials for tumor therapy.